PENGARUH PENGGUNAAN TEKNOLOGI DAN KUALITAS SISTEM INFORMASI AKUNTANSI TERHADAP SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) DI BKAD KABUPATEN ALOR - Yosua K. Laoepada; Indah Zakiyah (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2023)
The purpose of this study is (1) To determine the effect of the use of technology on the Regional Management Information System (SIMDA) in BKAD Alor Regency.(2). To determine the effect of the quality of the information system on the Regional Management Information System (SIMDA) in BKAD Alor Regency. (3). To determine the effect of the use of technology and the quality of information systems on the Regional Management Information System (SIMDA) in BKAD Alor Regency. The research design used is quantitative with phenomenology. It means explaining or expressing the meaning of a concept or phenomenon of experience which is based on the awareness that occurs by the individual. Sampling using purposive sampling of 49 people. The data analysis technique used is validity test, reliability test, classic assumption using SPSS version 16 program In the research method The type of research used in this study is to use a quantitative descriptive research type. Which emphasizes the analysis on numerical data (numbers) that are processed using statistical methods with a population of 62 accounting employees at the BKAD office of Alor Regency, East Nusa Tenggara Province with data analysis techniques, namely using multiple linear regression analysis. The results of the study, namely that as a whole, it can be concluded that the 49 respondents studied generally stated that: 1. The use of information technology has a significant positive effect on the regional management information system (SIMDA). This means that the better the use of technology, the regional management information system (SIMDA) obtained will be even better. 2. The quality of the accounting information system has a significant positive effect on the regional management information system (SIMDA). This means that the higher the quality of the accounting information system, the regional management information system (SIMDA) obtained will be better. 3. Regional information system (SIMDA) is influenced by the use of technology and the quality of information systems. This means that the better the use of technology and the quality of the information system, the regional management information system (SIMDA) obtained will be better. And the coefficient of determination, namely the Adjusted R Square value, is 0.609. This indicates that the variable contribution of the use of information technology and user switching is 60.90%, while the other 39.10% is determined by other factors outside the model not examined in this study.